2022
DOI: 10.3389/fcell.2022.840576
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Pyroptosis by ncRNA: A Novel Research Direction

Abstract: Pyroptosis is a novel form of programmed cell death (PCD), which is characterized by DNA fragmentation, chromatin condensation, cell swelling and leakage of cell contents. The process of pyroptosis is performed by certain inflammasome and executor gasdermin family member. Previous researches have manifested that pyroptosis is closely related to human diseases (such as inflammatory diseases) and malignant tumors, while the regulation mechanism of pyroptosis is not yet clear. Non-coding RNA (ncRNA) such as micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 129 publications
0
8
0
Order By: Relevance
“…The epigenetic regulation of pyroptosis may also depend on the action of small non-coding RNAs. It is known that several miRNAs bind to 3′-untranslated NLRP3 gene region and degrade it [104]. To confirm these evidences, it was demonstrated that during myeloid differentiation, low levels of miR-233 increases NLRP3 inflammasome transcription, accompanied by the release of pro-inflammatory cytokines in activated macrophages [105].…”
Section: Epigenetic Regulation In Pyroptosismentioning
confidence: 94%
“…The epigenetic regulation of pyroptosis may also depend on the action of small non-coding RNAs. It is known that several miRNAs bind to 3′-untranslated NLRP3 gene region and degrade it [104]. To confirm these evidences, it was demonstrated that during myeloid differentiation, low levels of miR-233 increases NLRP3 inflammasome transcription, accompanied by the release of pro-inflammatory cytokines in activated macrophages [105].…”
Section: Epigenetic Regulation In Pyroptosismentioning
confidence: 94%
“…Other novel modes of cell death have recently been reported, including pyroptosis, necroptosis, and cytoproptosis. Although certain circRNAs (e.g., hsa_circ_0001836 [ 76 ], circNEIL3 [ 77 ], and has_circ_0007312 [ 78 ]) have been found to promote pyroptosis in some cancers, the role of circRNA-mediated pyroptosis in thyroid cancers remains largely unknown. While necropoptosis has been reported in TCs [ 79 ], studies on the circRNA-mediated progression of TC through necroptosis are still lacking.…”
Section: Circrnas and Their Roles In Regulating Tc Hallmarksmentioning
confidence: 99%
“…Reports indicate that miR-22 mediates neuroinflammatory cascades and cell death through pyroptosis [ 82 , 83 ]. Low levels of miR-22 in the peripheral blood of AD patients suggests that mimicking miR-22 function could aid in the reduction of pyroptosis.…”
Section: Mechanisms Of Mirnas In Dementia-related Diseasementioning
confidence: 99%